Analisis Perilaku Persalinan Komunitas Adat Terpencil di Wilayah Taman Nasional Bukit Duabelas Kabupaten Sarolangun Provinsi Jambi - guspianto, guspianto; Amir, Andy; Mekarisce, Arnild Augina (Media Kesehatan Masyarakat Indonesia, 2019)
The Remote Indigenous Communities (RIC) live in groups in the secondary forests of Jambi Province. The relatively primitive social, economic, cultural and environmental conditions cause RIC to have vulnerable behavior towards health problems, including childbirth. This study aims to analyze the childbirth behavior in RIC who is considered to be a high risk of complications. The study design is descriptive qualitative research to understand holistically social phenomena about childbirth behavior among RIC in the Bukit Duabelas National Park area at Sarolangun Regency-Jambi. Research informants were selected purposively including Mothers who had given birth, Husbands, Traditional Birth Attendants (TBAs), Tumenggung, and Midwives. This study found in general childbirth behavior of RIC was unsafe and had a high risk that could have an impact on maternal and infant mortality. This is likely influenced by the lack of knowledge, less supportive attitude, low of need perception, and health services have not been optimal. Living in scattered groups and habits of “melangun” are obstacles for providing health services. It is recommended to improve the implementation of the P4K program and integrated health service activities, create a maternity shelter, provide “RIC Care Mobile”, and approach with RIC community leaders (Tumenggung), and TBAs on the importance of safe delivery to maintain maternal health and safety.